Maqasid Al-Syari’ah Analysis of Dualism of Authority in Determining the Beginning of The Lunar Month: A Study of The Isbat of the Ministry of Religious Affairs and The Ikhbâr of the Council of Tarjih Muhammadiyah - Majid, Ilham (Proceeding International Conference on Religion, Science and Education, 2025)
The phenomenon of dualism of authority in determining the beginning of the Hijri month in Indonesia, manifested through the Isbat of the Ministry of Religious Affairs and the Ikhbâr of the Tarjih Council of Muhammadiyah, has long been a source of differences in the implementation of Muslim worship. Although these two institutions have their own legitimacy and followers, the differences in their decisions have the potential to cause social friction. In addition, administratively, the government faces challenges in coordinating national holidays and activities related to Islamic holidays. This research uses a qualitative method with a literature study approach. The sources studied include official documents of both institutions, fiqh books, as well as scientific works related to Maqasid Al-Shari’ah. Data analysis was conducted using the Maqasid Al-Syari’ah framework as an interpretation instrument. The Maqasid Al-Syari’ah framework is used as an analytical lens to understand how this dualism of authority affects the objectives of sharia, especially in the context of religious protection and unity of the ummah. Maqasid Al-Syari’ah reveals the importance of finding common ground that considers aspects of the ummah’s interests, the flexibility of Islamic law, and Indonesia’s socio-cultural context. In addition, a more integrative and inclusive approach is needed in determining the beginning of the Hijri month, which respects the formal authority of the government while accommodating the diversity of religious understanding. Recommendations include increasing inter-institutional dialogue, developing a comprehensive methodology, and strengthening public education on the complexity of this issue, with the ultimate goal of realizing the greater good of the people in accordance with the principles of Maqasid Al-Syari’ah.